2001
DOI: 10.1097/00054725-200108000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Colonic Mucosal Concentrations of 5-Aminosalicylic Acid Is Useful for Estimating Its Therapeutic Efficacy in Distal Ulcerative Colitis: Comparison of Orally Administered Mesalamine and Sulfasalazine

Abstract: We demonstrated that the colonic mucosal concentration of 5-ASA was significantly higher in the sulfasalazine group than in the mesalamine group. Furthermore, the concentrations of mucosal 5-ASA may be a good marker for the estimation of its efficacy in the treatment of ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 14 publications
5
62
1
2
Order By: Relevance
“…However, there have been few reports investigating the relationship between colonic mucosal concentrations of 5-ASA and its clinical efficacy. One study showed that tissue concentration of 5-ASA was much higher in patients who received oral and rectal 5-ASA by enema than in patients who had oral 5-ASA alone [65]. These results support the role of rectal 5-ASA as a first-line therapy for mild or moderately active distal UC, and offer guidelines for its use [65,67].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, there have been few reports investigating the relationship between colonic mucosal concentrations of 5-ASA and its clinical efficacy. One study showed that tissue concentration of 5-ASA was much higher in patients who received oral and rectal 5-ASA by enema than in patients who had oral 5-ASA alone [65]. These results support the role of rectal 5-ASA as a first-line therapy for mild or moderately active distal UC, and offer guidelines for its use [65,67].…”
Section: Discussionmentioning
confidence: 85%
“…Some studies have shown that clinical and histological remissions are more evident when 5-ASA is administered by enema when compared with oral administration, suggesting that the drug has a topical effect greater than systemic [45,46,65,66]. However, there have been few reports investigating the relationship between colonic mucosal concentrations of 5-ASA and its clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Idiosyncratic side effects such as interstitial nephritis, myocarditis, or pancreatitis are very rare even when oral and systemic forms of 5-ASA are used [19]. The effects of 5-ASA are dependent on the concentration in the colonic mucosa [28]. In Switzerland, a previous report revealed that the consumption rate of topical 5-ASAs was 31.6% compared with the 42.5% for oral 5-ASA [26].…”
Section: Treatmentmentioning
confidence: 99%
“…Bystrowska et al (2000) have performed the determination of 5-ASA in plasma and urine samples Simultaneous assay of 5-aminosalicylic acid and its metabolite 351 ORIGINAL RESEARCH by liquid chromatography following prior derivatization to its acetylated metabolite. Few procedures have been described for the estimation by liquid chromatography of 5-ASA in human ileocolonic biopsy (De Vos et al, 1992;Palumbo et al, 1995;Hussain et al, 1998;Naganuma et al, 2001). Therefore, the objective of this work is to present a one-step liquid-liquid extraction procedure before simultaneous determination of 5-ASA and its metabolite by HPLC in human plasma.…”
Section: Introductionmentioning
confidence: 99%